Exploring the optimal lower blood pressure boundary during endovascular thrombectomy in patients with large vessel occlusion - Yu-Ming Chang; Chun-Min Wang; Kang-Po Lee; Po-Chun Shen; Po-Yu Lin; Chi-Hung Liu; Sheng-Hsiang Lin; Chih-Hung Chen; Meng-Tsang Hsieh; Pi-Shan Sung (Journal of the Formosan Medical Association)
Background: Current guidelines advocate for maintaining BP level below 180/105 mmHg during EVT, determining the safe lower boundary remains primarily consensus-driven by experts. This study aims to delve into the correlation between various targets of lower boundary for systolic and diastolic BP (SBP and DBP) during EVT and 3-month functional outcomes. Methods: A cohort study was conducted across two EVT-capable centers, enrolling patients with large artery occlusion undergoing EVT within 8 h of stroke onset. Mean BP values during EVT were meticulously recorded, and logistic regression models were utilized to evaluate the correlation between outcomes and diverse lower boundary targets for SBP and DBP. Additionally, logistic regression models investigated the relationship between periprocedural BP variability and subsequent outcomes. Results: Among the 201 patients included, having a SBP higher than 130 or 140 mmHg showed an independent association with increased good functional outcomes at 3 months (adjusted odds ratio, aOR 2.80, 95% Cis, 1.26–6.39 for 140 mmHg; aOR 2.34, 95% Cis, 1.03–5.56 for 130 mmHg). Additionally, an SBP exceeding 130 mmHg was correlated with decreased 3-month mortality (aOR, 0.24, 95% CI 0.07–0.74). No significant relationship was observed between DBP and functional outcomes. Patients with higher periprocedural SBP coefficient variance exhibited a decreased rate of good functional outcomes at 3 months (aOR, 0.42, 95% CI, 0.18–0.96). Conclusion: A SBP range above 130–140 mmHg could potentially serve as a safe lower boundary during EVT, while minimizing BP fluctuations may correlate with improved post-EVT functional outcomes.